Analisis Sistem Pengendalian Internal Persediaan Barang Dagang Pada Perum Bulog Sub Divisi Regional Wil IV Maumere - Veronika Yulriska Tennis; Yosefina Andia Dekrita; Siktania Maria Diliana (GEMILANG: Jurnal Manajemen dan Akuntansi, 2023)
Inventories are the company's current assets which are quite material in number and are one of the important factors in supporting the company's activities. Because of that, good internal control must be carried out to protect inventory from theft, misappropriation, and damage. The purpose of this study is to determine whether rice supply control is effective. The method used in this research is descriptive qualitative method. Data collection was carried out through observation, interviews, documentation and analysis using the method developed by Milles and Huberman. The results showed that in the control environment indicators there was a dual function of receiving incoming and outgoing goods in the warehouse section due to a shortage of employees, the risk assessment still had fluctuations in rice supplies, indicators of control activity at Perum Bulog Maumere had authorization by authorized employees and every document in each transaction has a printed serial number, information and communication to support internal control already uses a computerized system so that data accuracy can be guaranteed, monitoring of rice supplies is also carried out periodically, namely daily, weekly and monthly.